Aji Saraswati Merapi-Merbabu: Transformasi Teks Bhimaswarga Sebagai Panduan Ritual Literasi di Gunung Lawu Abad Ke-16 - Wijayanto, Muhammad Heno; Suparta, I Made (Jumantara: Jurnal Manuskrip Nusantara, 2023)
Aji Saraswati (AS) is a text that contains guidelines for literacy rituals in the Shivaist tradition in Indonesia. In general, the majority of known AS texts originate from the Shivaism tradition in Bali, while the Javanese tradition is not yet widely known. This research discusses AS texts originating from the Javanese tradition, especially the Merapi-Merbabu scriptorium collection. The AS text originating from the Merapi-Merbabu scriptorium is a collection of fragments originating from the hipograms of the text Bhima Swarga (BhS). The aim of this research is to apply intertextuality studies between AS MM texts and BhS as their hypograms. The intertextuality study was then carried out by functional analysis based on the sequences in the hypograms text which were transformed into AS MM text. This research uses a qualitative approach. Philological work steps such as inventory, description, text comparison, text edition, and translation are carried out in this study to produce text editions that can be understood by the wider community. Rifattere's theory of intertextuality (expansion and conversion) and Pradotokusumo (modification and excerpt) is used in this study to determine the hypogrammatic phenomena in AS MM text from hipogram text. The results of this study are that there are eight text sequences that are transformed into AS MM text. The eight transformed sequences include: (1) Position of Goddess Saraswati; (2) Physiological elements (3) Trikaya Paramartha's association with aspects of manuscript production; (4) Position of vowel or swara characters; (5) The essence of the aspect of duality; (6) The Reality of Om Awighnamastu; (7) Literacy ritual spells; and (8) God's association with fire. The entire transformation sequence of hypograms text into AS MM text is a transformation from narrative prose text in strict form to mantra text. The text of the spell in AS MM is used in literacy rituals in the Merapi-Merbabu scriptorium environment.